2002
DOI: 10.1002/pits.10058
|View full text |Cite
|
Sign up to set email alerts
|

Increasing on‐task behavior during mathematics independent seat‐work in students with emotional disturbance by interspersing additional brief problems

Abstract: Alternating treatments designs were used to compare on‐task levels in 4 students diagnosed as emotionally disturbed while working on control and experimental independent seat‐work mathematics assignments. Control and experimental assignments were similar except experimental assignments contained additional briefer mathematics problems interspersed following every third problem. Results showed greater on‐task levels while working on experimental assignments across 3 of the 4 students. Discussion focuses on prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…For example, a single-digit multiplication problem may be interspersed after every third four-digit multiplication problem (e.g., Cates & Skinner, 2000). Research has demonstrated that this and similar strategies not only increases task performance but also decreases disruptive behavior (e.g., Skinner, Hurst, Teeple, & Meadows, 2002). An added benefit is improvements in student perceptions of, and preferences for, assignments that were previously considered difficult (e.g., Cates & Skinner, 2000).…”
Section: Examplesmentioning
confidence: 97%
“…For example, a single-digit multiplication problem may be interspersed after every third four-digit multiplication problem (e.g., Cates & Skinner, 2000). Research has demonstrated that this and similar strategies not only increases task performance but also decreases disruptive behavior (e.g., Skinner, Hurst, Teeple, & Meadows, 2002). An added benefit is improvements in student perceptions of, and preferences for, assignments that were previously considered difficult (e.g., Cates & Skinner, 2000).…”
Section: Examplesmentioning
confidence: 97%
“…These types of intervention has also been found to improve work completion and on-task behavior (Dunlap, Kern-Dunlap, & Clarke, 1991;Kern et al, 1994). In the general education classroom, teachers can modify assignments to match instruction to the skill level of the student (Moore et al, 2005;Umbreit et al, 2004), adjust content and format of lessons, (Kern et al, 1994), reduce the duration of the task (Kern et al, 1994;Moore et al, 2005), provide a peer tutor (Newcomer & Lewis, 2004), or mix easy and difficult problems together (Cates & Erkfritz, 2007;McCurdy, Skinner, Grantham, Watson, & Hindman, 2001;Skinner, Hurst, Teeple, & Meadows, 2002). Given that academic skill deficits may be a contributing factor for students displaying escape maintained behaviors, it is vital that academic skills be evaluated and any academic skills deficit identified so that effective academic instructional supports as provided.…”
Section: Curricular and Instructional Revisionmentioning
confidence: 97%
“…One procedure for doing this is to intersperse additional very brief discrete tasks among longer discrete tasks. Such procedures have been shown to enhance on-task levels and the probability of students choosing assignments that require more effort to complete as opposed to less effort (Billington, Skinner, & Cruchon, 2004;Billington, Skinner, Hutchins, & Malone, 2004;Cates & Skinner, 2000;McCurdy, Skinner, Grantham, Watson, & Hindman, 2001;Skinner, Hurst, Teeple, & Meadows, 2002).…”
Section: Reinforcersmentioning
confidence: 97%